How to interpret the ethical dimension in medicine? Ethical dimension in medicine - Petralia, Paolo; Doldi, Marco (Medicina Historica, 2022)
All behaviors in medical practice, over time and in the various operating modes, are intrinsically human. However, they require explicit awareness in order to be understood and interpreted properly as such. The search for the question "who is man” has always involved every man - as well as the arts and sciences. To find this answer, science is not enough. It is necessary to refer to concepts drawn from anthropology and face to ethical dilemmas. Combining anthropology and ethics in the bioethical perspective allows us to deeply establish the necessary and ineliminable meaning that human life intrinsically possesses from its first instant to its natural end. There are two dimensions that characterize man in a unique way: corporeality and spirituality. These are the general and fundamental conditions within which to move to answer of this fundamental question. Based on this response, the composition of acting in medicine for the healthcare professional can take place, as well as the re-construction of an authentic interpersonal relationship between physician and patient.